ANALISIS KOMPETENSI PROFESIONAL CALON GURU PAI IAIN BATUSANGKAR BERDASARKAN GENDER - Rizki Pebrina (AGENDA: Jurnal Analisis Gender dan Agama, 2019)
Having professional competence is a must for prospective teachers. Professional competence of Islamic Education prospective teacher can be seen from the ability to master the theories of Islamic Education. Based on the author's observations on their abilities in mastering and explaining the theories, female prospective teachers are better than male prospective teachers. This research was conducted through observation. The research result shows the professional competence of prospective teachers of Islamic Education in sufficient category. Based on gender, female students gain better competence (59,9%) than male students (55,2%).